Quad-heterostructure precipitation-strengthened high-entropy alloy overcomes strength-ductility trade-off from cryogenic to intermediate temperatures - J.X. Zhu; Shiwei Wu; C. Ren; Yuefei Jia; B.X. Cao; J.L. Ren; T. Yang; P.K. Liaw; G. Wang (Materials Research Letters)
We use a multi-heterostructure strategy to mitigate temperature-induced brittleness and strain-softening in precipitation-strengthened high-entropy alloys (PSHEAs). A PSHEA consisting of four types of heterostructures, including deformed/recrystallization grains bands inside with irregularly-shaped/spheroidal coherent precipitates, and smooth/serrated grain and precipitate-matrix interfaces, is successfully synthesized. The resultant PSHEA exhibits significantly-enhanced strength and uniform elongation simultaneously at −196–700 °C. This overcoming of the strength-ductility trade-off is attributed to a synergistic hetero-deformation-induced strengthening effect, and a two-level strain-delocalization toughening effect. Our findings offer a promising pathway to develop ultra-strong, ductile, and strain-hardenable PSHEAs and superalloys in a wide temperature range.